2020
DOI: 10.1016/j.abd.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of staged excision with pathologic margin control in high-risk basal cell carcinoma of the head region

Abstract: Background High-risk basal cell carcinoma involves a significant rate of basal cell carcinoma that requires Mohs micrographic surgery for definitive treatment. Staged excision with pathologic margin control is a simple, accessible, and curative procedure suggested for the treatment of high-risk basal cell carcinoma. Objective To evaluate the results of staged excision of high-risk basal cell carcinoma in the head region. Methods This interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Devine et al (2017) similarly identified a younger sample in Great Britain, with a mean age of 72.5 years [21]. We also reviewed other studies where, in contrast to our data, the majority of subjects were male [3,[22][23][24]. Ghanadan et al (2014) attributed this gender distribution to factors such as women's higher usage of SPF face protection products and men's increased outdoor exposure leading to greater direct UV radiation exposure [25].…”
Section: Discussioncontrasting
confidence: 52%
“…Devine et al (2017) similarly identified a younger sample in Great Britain, with a mean age of 72.5 years [21]. We also reviewed other studies where, in contrast to our data, the majority of subjects were male [3,[22][23][24]. Ghanadan et al (2014) attributed this gender distribution to factors such as women's higher usage of SPF face protection products and men's increased outdoor exposure leading to greater direct UV radiation exposure [25].…”
Section: Discussioncontrasting
confidence: 52%
“…Devine et al (2017) similarly identified a younger sample in Great Britain, with a mean age of 72.5 years [ 21 ]. We also reviewed other studies where, in contrast to our data, the majority of subjects were male [ 3 , 22 , 23 , 24 ]. Ghanadan et al (2014) attributed this gender distribution to factors such as women’s higher usage of products containing SPF (sun protection factor) for face protection from ultraviolet (UV) rays and men’s increased outdoor exposure leading to greater direct UV radiation exposure [ 25 ].…”
Section: Discussionmentioning
confidence: 86%
“…1,2 Surgical excision is the most common treatment associated with high clearance rates, at an expense of aesthetic and functional morbidity, especially in T-zone lesions. 3 Currently, clinical guidelines 4 advocate that the selection of treatment plans should base on the pathological subtype of BCC. Non-surgical treatments are recommended for sBCC because it is the thinnest of all the subtypes of BCC and generally does not grow aggressively.…”
Section: Introductionmentioning
confidence: 99%
“…Superficial basal cell carcinoma (sBCC) is a common subtype of basal cell carcinoma (BCC), which is generally considered to be a non‐aggressive form of skin malignancy and accounts for ~10–17% of all BCC 1,2 . Surgical excision is the most common treatment associated with high clearance rates, at an expense of aesthetic and functional morbidity, especially in T‐zone lesions 3 . Currently, clinical guidelines 4 advocate that the selection of treatment plans should base on the pathological subtype of BCC.…”
Section: Introductionmentioning
confidence: 99%